Amistades apasionadas: Reflexiones en torno a las representaciones masculinas presentes en la película argentina Soñar, soñar, de Leonardo Favio - Navone, Santiago (2015)
The aim of this article is to analyze the ambiguous characteristics of the male representations in Leonardo Favio’s Soñar, soñar (1976). Favio was one of the most popular directors of the period. His films always present figures related to Argentina’s popular classes. In Soñar, soñar, Carlos, a young man from a small town (played by Carlos Monzón) and a popular Argentine boxing champion, meets Mario, an urban artist (played by Gian Franco Pagliaro) and a popular Argentine singer. Carlos decides to travel with Mario to Buenos Aires to become an artist himself. The affective relationship between the characters is ambiguous and exceeds the usual boundaries of Argentine homosocial bonds. Specifically, Carlos’s character is a “country man” in a performance that, intensifying sentimentalism and ridicule, vindicates his subaltern position, thus exceeding the usual limits of the traditional Argentine conceptions of masculinity. These disruptive male figures are displayed in a plot with elements of popular melodrama.